Scale effects on a single-element inverted wing in ground effect. (July 2014) - Correia, J.; Roberts, L. S.; Finnis, M. V.; Knowles, K.
Abstract: A study was conducted on a GA(W)-1 wing in order to investigate the effect of testing inverted wings in ground effect at low Reynolds numbers. The wing was tested at a range of ground clearances and Reynolds numbers and results showed that the wing's performance was dependent on both these parameters. Surface flow-visualisation and numerical simulation results highlighted the existence of a laminar separation bubble on the wing's suction surface. The results also indicated that both the bubble's length and the onset of separation were sensitive to ground clearance and Reynolds number. Attempts were made to minimise the wing's Reynolds number dependency by using transition strips on the suction surface. The transition strip results highlighted the influence that a laminar separation bubble has on the overall performance of the wing and how its presence alters the force enhancement and reduction mechanisms on an inverted wing in ground effect.